2020
DOI: 10.3390/w12041178
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Benefits of Forested Riparian Zones: A Qualitative Index of Riparian Integrity Is Positively Associated with Ecological Status in European Streams

Abstract: Developing a general, predictive understanding of ecological systems requires knowing how much structural and functional relationships can cross scales and contexts. Here, we introduce the CROSSLINK project that investigates the role of forested riparian buffers in modified European landscapes by measuring a wide range of ecosystem attributes in stream-riparian networks. CROSSLINK involves replicated field measurements in four case-study basins with varying levels of human development: Norway (Oslo Fjord), Swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(103 citation statements)
references
References 72 publications
4
97
0
2
Order By: Relevance
“…The proportion of taxa from the orders Ephemeroptera, Plecoptera and Trichoptera is also known as the proportion of EPT taxa or simply EPT. Average score per taxon (ASPT) values were also derived, as described in Monaghan and Soares [37] and Burdon et al [38] to detect potential loading with organic matter, which could influence the macroinvertebrate community structure. Correlations between explanatory variables and the structure of the macroinvertebrate community were tested with a Kendall tau rank correlation coefficient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proportion of taxa from the orders Ephemeroptera, Plecoptera and Trichoptera is also known as the proportion of EPT taxa or simply EPT. Average score per taxon (ASPT) values were also derived, as described in Monaghan and Soares [37] and Burdon et al [38] to detect potential loading with organic matter, which could influence the macroinvertebrate community structure. Correlations between explanatory variables and the structure of the macroinvertebrate community were tested with a Kendall tau rank correlation coefficient.…”
Section: Discussionmentioning
confidence: 99%
“…Błachuta et al [55] report that ASPT is most susceptible to water flow, while Monaghan and Soares [37] report that ASPT is positively correlated with flow velocity and substrate diversity. Surprisingly, Burdon et al [38] found that ASPT is negatively influenced by improving riparian condition. However, we failed to find a significant correlation between ASPT and human alterations of riparian zone or morphological conditions.…”
Section: Correlations Between Environmental Factors and Diversity Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Intact habitat along the 100-m riparian mask of streams, while more abundant in northern MI, MI, and WI, was considerably more evenly distributed throughout the study area than was upstream habitat. Riparian buffers are frequently employed to mitigate the effects of agricultural input, and are frequently the only remaining forested habitat in agricultural watersheds (Craig et al 2008;Burdon et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The range and status of riparian vegetation is not only related to the integrity index of rivers evaluated through the macroinvertebrate index, which was commonly used, but also affects the overall of the riverine landscape attributes. In this respect, the management of the riparian vegetation is of paramount importance to conserve biodiversity in river ecosystems at a time of rapid environmental change and increasing pressure from a range of human influences, including habitat loss, pollution, and climate change [42].…”
Section: Introductionmentioning
confidence: 99%